The Application of Plea Bargaining and Restorative Justice in Criminal Trials in Nigeria. (Global Journal of Human-Social Science, 2019)
The use of plea bargaining concept in the dispensation of criminal trials in Nigeria is highly debatable. Critics see it as a violation of the accused person's fundamental rights while advocates see it as the most useful instrument for quick disposal of criminal cases. This paper explores the position of the laws relating to plea bargaining in other jurisdictions and makes recommendations for incorporation into our laws. In conducting this study a jurisprudential analysis has been carried out with the help of statutes and judicial authorities. The paper has found that the use of plea bargaining in Nigeria cuts short the delay of criminal cases and save the time and energy of the accused, prosecution and the State. The paper suggests that if Nigeria desires to practise plea bargaining, she needs to enact into her constitution, standard procedure rules regulating the concept, borrowing some lessons from India and Pakistan models.
Keywords: criminal trials; plea bargaining; criminal procedure; speedy disposal; restorative justice